Clinical Characteristics of Acute Kidney Injury in COVID-19 Patients - Nisrina, Nada; Wibowo, Resna Murti (Muhammadiyah Medical Journal, 2023)
Background: Coronavirus Disease 2019 (COVID-19) is one of the infectious diseases that exist in Indonesia. Not only infects the lungs, but this virus can also infect other organs such as the kidneys. In addition, the process of viral infection causes cell hypermetabolism, which can increase the workload of the kidneys in excreting metabolic waste. In the end, the damage caused by the virus can cause Acute Kidney Injury (AKI). It is necessary to know the prevalence and characteristics of this event. Purposes: This study aims to provide an overview of AKI's prevalence and clinical features in COVID-19 patients. Methods: This was a descriptive study that used patient medical records for the period April-September 2021. The univariate analysis data showed a characteristic frequency distribution of age, gender, comorbidity, hospitalization duration, and urea creatinine rate. Results: The incoming samples based on the inclusion and exclusion criteria were 44 samples. In COVID-19 patients, complications of AKI were found in adults, as much as 68.2% of both men and women had a percentage of 50%, the most common comorbid was hypertension 30.8% with a hospitalization duration of 1-10 days 43.2% and an average increase in urea 79.68 mg/dL and creatinine average 2,859 mg/dL. Conclusion: Based on patient characteristics, the results showed that more COVID-19 patients with acute kidney injury complications occurred in adult patients, with no difference in prevalence between males and females, with comorbid hypertension and length of hospitalization less than ten days.